The Role of Media and Mass Communication Theory in the Global Pandemic - Deuze, Mark (Communication Today, 2020)
Throughout the history of the field of media and mass communication theory and research, claims have been made that ‘mass’ media and ‘mass’ communication are concepts that do not fit the contemporary media environment (anymore). However, contemporary developments and debates regarding the role of media and communication in the context of a global pandemic clearly suggest otherwise. In this article, the field of study regarding media and mass communication is reviewed based on the (7) fundamental theories explaining the role of media in society, as these have emerged out of a century of scholarship in media studies and communication science. The study aims to show how each of these theories can be considered to be ‘at work’ in current debates and concerns about the role of media and communication in the global coronavirus pandemic/infodemic.